A high entropy layered oxide material, preparation method, positive electrode sheet, and secondary battery

By doping large ion radius potassium metal elements in situ in sodium ion batteries, the high entropy layered oxide material NaaKxNibFecMndCueTifMgO2+β is prepared, which solves the problem of poor capacity and circulation performance of the positive electrode material of sodium ion batteries, and achieves high circulation performance and safety Improved performance, suitable for the positive electrode material of sodium ion secondary batteries.

CN119069710BActive Publication Date: 2025-01-17HUNAN ZHENGYUAN ENERGY STORAGE MATERIALS & DEVICE INST
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411559801.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-01-17
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The actual capacity of the positive electrode material in existing sodium ion batteries is low, the cycle performance is poor, and the effective in-situ doping large ion radius method is lacking for the preparation of high-entropy layered oxide materials.

Method used

By doping large ion radius potassium metal elements in situ in the sodium layer, the high entropy layered oxide material NaaKxNibFecMndCueTifMgO2+β is prepared by in-situ doping large ion radius potassium metal elements in the sodium layer, and charging and discharging are used to use solid phase method, spray drying method, sol-gel method and co-precipitation method, and The current size and cycle number determine the amount of potassium ion incorporation and enhance the structural strength.

Benefits of technology

It has achieved high entropy layered oxide materials with high cycling performance, good safety performance and high average discharge voltage, and has great development potential and is suitable for the positive electrode materials of sodium ion secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119069710B_ABST
    Figure CN119069710B_ABST
Patent Text Reader

Abstract

The present invention discloses a high entropy layered oxide material, a preparation method, a positive electrode sheet, and a secondary battery. The general chemical formula of the material is: Na a K x Ni b Fe c Mn d Cu e Ti f M g O 2+β , where K is located in the sodium layer, Ni 、 Fe 、 Mn 、 Cu 、 Ti 、 M is located in the transition metal layer, where 0.7
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy materials, and in particular to a high-entropy layered oxide material, a preparation method, a positive electrode sheet, and a secondary battery. Background Art

[0002] In recent years, the development of sodium-ion batteries has received increasing attention. The working principle of sodium-ion batteries is similar to that of lithium-ion batteries. During charging and discharging, sodium ions are reversibly intercalated and deintercalated in the structure of the positive and negative electrode host materials. Sodium-ion batteries have a suitable redox potential [relative to standard hydrogen electrode, E(Na / Na + ) = -2.71 V, E(Li / Li + ) is 0.3 V higher]. In addition, sodium does not react with aluminum to form an alloy, so sodium-ion batteries can use aluminum foil as the current collector for the positive and negative electrode materials, replacing the more expensive, more costly, and heavier copper current collector, thereby reducing battery costs while increasing energy density.

[0003] At present, sodium-ion batteries have low actual capacity and poor cycle performance, and there is still a lot of room for development compared with lithium-ion batteries. The key characteristics of batteries (such as specific capacity, cycle performance and working platform voltage) are mainly determined by the inherent electrochemical properties of the positive and negative electrode materials of the battery. Therefore, the primary goal in the current sodium-ion battery research system is to find suitable electrode materials, especially positive electrode materials, which largely determine the energy density and safety performance of the battery. Among them, the layered transition metal oxide positive electrode material Na x MO2 (M = Fe, Mn, Ni, Co, Al, etc. and their combinations) has attracted wide attention due to its high energy density and simple synthesis, and has great application potential. However, with the deep deintercalation of sodium ions, the transition metal layer will undergo relative slip, resulting in structural rearrangement and complex phase transitions during the charge and discharge process. Zheng et al. prepared O3 phase Na 0.9 Ni 0.45 Mn 0.4 Ti 0.15 O2 layered oxide material was electrochemically characterized and its capacity retention rate was only 75% after 30 cycles in the voltage window of 1.5V–4.5V.

[0004] In the transition metal layer of the layered cathode material for sodium-ion batteries, the transition metal elements of the third period are mainly used, and there are many existing related researches and reports. Doping the sodium layer with a large ionic radius potassium metal element is considered an effective method to inhibit the high-pressure phase transition of layered oxides. The general doping method is mainly the solid-phase sintering method, and its disadvantages are as follows: 1. The potassium carbonate raw material has strong hygroscopicity, and the aqueous solution is alkaline, requiring a relatively high environmental requirement for the preservation of the raw materials. 2. The doping amount cannot be accurately controlled, and there will be losses, and the element stoichiometry needs to be excessive. And there is currently no in-situ doping method for large ionic radius for the related reports of the layered oxide cathode material for sodium-ion batteries with high entropy. Summary of the Invention

[0005] The present invention provides a method for preparing a high-entropy layered oxide material by in-situ doping and its application, doping a large ionic radius metal element in the sodium layer. The high-entropy layered oxide material is simple to prepare, has a high first-cycle efficiency, a relatively high average discharge voltage, good cycling performance, good safety performance, and has great development potential.

[0006] In the first aspect, the present invention provides a high-entropy layered oxide material by in-situ doping, and the chemical general formula is: Na a K x Ni b Fe c Mn d Cu e Ti f M g O 2+β , where a, x, b, c, d, e, f, g, 2+β are the molar percentages of the corresponding elements respectively, and doping the large ionic radius potassium metal element in the sodium layer through the form of charge and discharge plays a role in stabilizing the layered structure;

[0007] Among them, M is the element for doping and substitution in the transition metal layer, specifically one or more elements among magnesium, zinc, vanadium, chromium, zirconium, niobium, molybdenum, ruthenium, tin, antimony, aluminum, etc. The relationship between the molar percentages satisfies b + c + d + e + f + g = 1, and a + x + 2b + 3c + 4d + 2e + 4f + mg = 2(2 + β); where 0.7 < a ≤ 1; 0 < x ≤ 0.1; 0.05 < b ≤ 0.35; 0.05 < c ≤ 0.2; 0.05 < d ≤ 0.35; 0 < e ≤ 0.1; 0.05 < f ≤ 0.2; 0 < g ≤ 0.1; -0.02 ≤ β ≤ 0.02; m is the valence state of the M element.

[0008] The crystal structure of the high-entropy layered oxide material is the O3 phase, and the space group is R3m. The material Na a K x Ni b Fe c Mn d Cu e Tif M g O 2+β Elements such as Ni and Fe participate in the process of gaining and losing electrons, while elements such as Mn and Ti play a role in stabilizing the structure.

[0009] Preferably, the high entropy layered oxide material is used as a positive electrode active material for a sodium ion secondary battery.

[0010] In a second aspect, the present invention provides a method for preparing the high entropy layered oxide material as described in the first aspect, wherein the method is a solid phase method + in-situ method, comprising:

[0011] Sodium carbonate containing 90 wt% to 112 wt% of the required sodium stoichiometry and nickel oxide, manganese dioxide, iron oxide, titanium dioxide, copper oxide and oxide of M (one or more elements selected from magnesium, zinc, vanadium, chromium, zirconium, niobium, molybdenum, ruthenium, tin, antimony, aluminum, etc.) containing the required stoichiometric amounts are mixed in proportion to form a precursor.

[0012] The precursors are uniformly mixed by ball milling to obtain precursor powder.

[0013] The precursor powder is placed in a muffle furnace and heat treated in an air atmosphere at 600° C. to 1000° C. for 5 to 25 hours.

[0014] The precursor powder after heat treatment is ground and sieved to obtain high entropy Na a Ni b Fe c Mn d Cu e Ti f M g O 2+β Layered oxide materials.

[0015] The material is made into a positive electrode, and a potassium sheet is used as a negative electrode for electrochemical assembly. The electrolyte is a solution of 1.0 mol / L NaPF6 + 5% KPF6 dissolved in ethylene carbonate and diethyl carbonate, and 0.1C charge and discharge is performed in the voltage range of 1.5-4.5V. After completing 2-10 cycles, the high entropy Na a K x Ni b Fe c Mn d Cu e Ti f M g O 2+β Layered oxide materials.

[0016] In a third aspect, the present invention provides a method for preparing the high entropy layered oxide material as described in the first aspect, wherein the method is a spray drying method + an in-situ method, comprising:

[0017] A mixture of sodium nitrate, nickel acetate, manganese acetate, iron acetate, copper acetate, titanium nitrate and nitric acid or acetate of M (one or more elements such as magnesium, zinc, vanadium, chromium, zirconium, niobium, molybdenum, ruthenium, tin, antimony, aluminum, etc.) in corresponding stoichiometric ratios is used as a precursor.

[0018] The precursor mixture is added with ethanol or water and stirred evenly to form a slurry.

[0019] The slurry is spray-dried to obtain a precursor powder.

[0020] The precursor powder is placed in a muffle furnace and heat treated in an air atmosphere at 600° C. to 1000° C. for 5 to 25 hours.

[0021] The heat-treated precursor powder is ground and sieved to obtain high entropy Na a Ni b Fe c Mn d Cu e Ti f M g O 2+β Layered oxide materials.

[0022] The material is made into a positive electrode, and a potassium sheet is used as a negative electrode for electrochemical assembly. The electrolyte is a solution of 1.0 mol / L NaPF6 + 5% KPF6 dissolved in ethylene carbonate and diethyl carbonate, and 0.1C charge and discharge is performed in the voltage range of 1.5-4.5V. After completing 2-10 cycles, the high entropy Na a K x Ni b Fe c Mn d Cu e Ti f M g O 2+β Layered oxide materials.

[0023] In a fourth aspect, the present invention provides a method for preparing the high entropy layered oxide material as described in the first aspect, wherein the method is a sol-gel method + an in-situ method, comprising:

[0024] Sodium acetate or sodium nitrate or sodium carbonate or sodium sulfate with a stoichiometric amount of 90wt% to 112wt% of the required sodium, and nitrates or sulfates containing elements such as nickel, manganese, iron, copper, titanium and M (one or more elements selected from magnesium, zinc, vanadium, chromium, zirconium, niobium, molybdenum, ruthenium, tin, antimony, aluminum, etc.) are dissolved in water or ethanol in a stoichiometric ratio and mixed into a precursor solution.

[0025] The mixture is stirred at 50° C. to 100° C., and a proper amount of a chelating agent is added, followed by evaporation to form a precursor gel.

[0026] The precursor gel is placed in a crucible and pre-fired in an air atmosphere at 100-600° C. for 1-3 hours.

[0027] Then heat treat at 600℃~1000℃ for 5~25 hours.

[0028] The heat-treated precursor powder is ground and sieved to obtain high entropy Na a Ni b Fe c Mn d Cu e Ti f M g O 2+β Layered oxide materials.

[0029] The material is made into a positive electrode, and a potassium sheet is used as a negative electrode for electrochemical assembly. The electrolyte is a solution of 1.0 mol / L NaPF6 + 5% KPF6 dissolved in ethylene carbonate and diethyl carbonate, and 0.1C charge and discharge is performed in the voltage range of 1.5-4.5V. After completing 2-10 cycles, the high entropy Na a K x Ni b Fe c Mn d Cu e Ti f M g O 2+β Layered oxide materials.

[0030] In a fifth aspect, the present invention provides a method for preparing the high entropy layered oxide material as described in the first aspect above, wherein the method is a co-precipitation method + an in-situ method, comprising:

[0031] Nitrates or sulfates or carbonates or hydroxides of elements such as nickel, manganese, iron, copper, titanium and M (one or more elements of magnesium, zinc, vanadium, chromium, zirconium, niobium, molybdenum, ruthenium, tin, antimony, aluminum, etc.) in a required stoichiometric ratio are dissolved in a certain volume of deionized water to form solutions.

[0032] The solution is slowly added dropwise into an ammonia solution of a certain concentration and a pH value of 6-10 to generate a precipitate.

[0033] The obtained precipitate is cleaned with deionized water, dried, and uniformly mixed with sodium carbonate according to a stoichiometric ratio to obtain a precursor.

[0034] The precursor is placed in a crucible and heat treated for 5 to 25 hours in an air atmosphere at 600 to 1000° C. to obtain a precursor powder.

[0035] The heat-treated precursor powder is ground and sieved to obtain high entropy Na a Ni b Fe c Mn d Cu e Ti f M g O 2+β Layered oxide materials.

[0036] The material is made into a positive electrode, and a potassium sheet is used as a negative electrode for electrochemical assembly. The electrolyte is a solution of 1.0 mol / L NaPF6 + 5% KPF6 dissolved in ethylene carbonate and diethyl carbonate, and 0.1C charge and discharge is performed in the voltage range of 1.5-4.5V. After completing 2-10 cycles, the high entropy Na a K x Ni b Fe c Mn d Cu e Ti f M g O 2+β Layered oxide materials.

[0037] In a sixth aspect, the present invention provides a positive electrode sheet for a sodium ion secondary battery, the positive electrode sheet comprising:

[0038] A current collector, a conductive additive coated on the current collector, a binder and the high entropy Na a K x Ni b Fe c Mn d Cu e Ti f M g O 2+β Layered oxide materials.

[0039] In a seventh aspect, the present invention provides a use of the sodium ion secondary battery described in the sixth aspect, wherein the sodium ion secondary battery is used for large-scale energy storage equipment for solar power generation, heavy industry, backup mobile power supplies or communication base stations.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] The high entropy Na a K x Ni b Fe c Mn d Cu e Ti f M g O 2+β The preparation method of layered oxide material dopes potassium metal element with large ion radius into the sodium layer, and uses the size of charge and discharge current and the number of cycles to determine the amount of potassium ion doping. KK dimer fixes the sodium layer to enhance the structural strength. It has good cycle performance, good safety performance, high average discharge voltage, and has great practical potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The Na provided in Example 1 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zn 0.1 XRD pattern of O2.

[0043] Figure 2 The Na provided in Example 1 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zn 0.1 SEM image of O2.

[0044] Figure 3 Example 1 provides Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zn 0.1 SEM image of O2.

[0045] Figure 4 This is a battery charge and discharge curve diagram provided in Example 1. DETAILED DESCRIPTION

[0046] In order to better understand the technical solution provided by the present invention, the following uses a plurality of specific examples to illustrate the use of several methods provided by the present invention to prepare high entropy Na a K x Ni b Fe c Mn d Cu e Ti f M g O 2+β Specific processes for layered oxide materials.

[0047] Example 1

[0048] In this embodiment, a high temperature solid phase method + in-situ method is used to prepare a layered oxide material, including:

[0049] Sodium carbonate, nickel oxide, manganese oxide, iron oxide, titanium oxide, copper oxide, (the oxide of M is zinc oxide, and the raw materials are all analytically pure) are mixed according to the required stoichiometric ratio (sodium carbonate 0.95 mol, nickel oxide 0.35 mol, manganese oxide 0.3 mol, iron oxide 0.1 mol, titanium oxide 0.1 mol, copper oxide 0.05 mol, zinc oxide 0.1 mol); ball milling is performed on a ball mill at 400 rpm for 10 hours to obtain a precursor; the precursor mixture is transferred to an aluminum oxide crucible and treated at 950°C in a muffle furnace for 15 hours to obtain a black powder layered oxide material Na 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zn 0.1 O2. Figure 2 : is a SEM image of the material, and its average particle diameter is about 15-50 microns.

[0050] The high entropy layered oxide material prepared above is used as the positive electrode material of the battery. The specific steps are as follows: 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zn 0.1 O2 powder is mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 95:2:3, and an appropriate amount of N-methylpyrrolidone solution is added to stir and form a slurry. The slurry is then evenly coated on aluminum foil and cut into electrodes after vacuum or blast drying. Dry at 80°C for 12 hours under vacuum conditions and then transfer to a glove box for use.

[0051] The battery was assembled in an argon atmosphere glove box, with a potassium metal sheet as the negative electrode and a NaPF6+5%KPF6 / diethyl carbonate solution as the electrolyte. The battery was charged and discharged for 8 cycles at a current density of 0.1 C. The positive electrode was then removed, disassembled, crushed, cleaned, and fully dried to obtain Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zn 0.1 O2 was tested by XRD, and its XRD spectrum can be found in Figure 1 Its crystal structure is an oxide with an O3 phase layered structure. Figure 3 The SEM image of the material shows that the average particle diameter is about 12 microns. The electrochemical performance of the obtained positive electrode is tested with metallic sodium as the negative electrode. Under the conditions of a discharge cut-off voltage of 1.5V and a charge cut-off voltage of 4.5V, the test results are shown in FIG. Figure 4 . Figure 4 The charge and discharge cycle curves of the first and tenth cycles are shown. The first cycle discharge specific capacity is 171 mAh / g, the first cycle coulombic efficiency is about 91%, and the capacity retention rate is about 90% after 100 cycles at a 0.2C rate. The data is shown in Table 1.

[0052] Example 2

[0053] In this embodiment, a high temperature solid phase method + in-situ method is used to prepare a layered oxide material, including:

[0054] Sodium carbonate, nickel oxide, manganese oxide, iron oxide, titanium oxide, copper oxide, (the oxide of M is zinc oxide, and the raw materials are all analytically pure) are mixed in the required stoichiometric ratio (sodium carbonate 0.95 mol, nickel oxide 0.35 mol, manganese oxide 0.3 mol, iron oxide 0.1 mol, titanium oxide 0.1 mol, copper oxide 0.05 mol, zinc oxide 0.1 mol); ball milling is performed on a ball mill at 400 rpm for 6 hours to obtain a precursor; the precursor mixture is transferred to an aluminum oxide crucible and treated in a muffle furnace at 950°C for 15 hours to obtain a black powder layered oxide material Na 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zn 0.1 O2.

[0055] The high entropy layered oxide material prepared above is used as the positive electrode material of the battery. The specific steps are as follows: 0.9 Ni0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zn 0.1 O2 powder is mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 95:2:3, and an appropriate amount of N-methylpyrrolidone solution is added to stir and form a slurry. The slurry is then evenly coated on aluminum foil and cut into electrodes after vacuum or blast drying. Dry at 80°C for 12 hours under vacuum conditions and then transfer to a glove box for use.

[0056] The battery was assembled in an argon atmosphere glove box, with a potassium metal sheet as the negative electrode and a NaPF6+5%KPF6 / diethyl carbonate solution as the electrolyte. The battery device was assembled. The charge and discharge cycle test was performed at a current density of 0.1 C for 2 cycles. The positive electrode was then taken out, disassembled, crushed, cleaned, and finally dried to obtain Na 0. 9K 0.02 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zn 0.1 O2, the positive electrode is obtained and then the electrochemical performance is tested using metallic sodium as the negative electrode. Under the conditions of a discharge cut-off voltage of 1.5V and a charge cut-off voltage of 4.5V, the test results are shown in Table 1.

[0057] Example 3

[0058] In this embodiment, a high temperature solid phase method + in-situ method is used to prepare a layered oxide material, including:

[0059] Sodium carbonate, nickel oxide, manganese oxide, iron oxide, titanium oxide, copper oxide, (the oxide of M is zinc oxide, and the raw materials are all analytically pure) are mixed in the required stoichiometric ratio (sodium carbonate 0.95 mol, nickel oxide 0.35 mol, manganese oxide 0.3 mol, iron oxide 0.1 mol, titanium oxide 0.1 mol, copper oxide 0.05 mol, zinc oxide 0.1 mol); ball milling is performed on a ball mill at 400 rpm for 6 hours to obtain a precursor; the precursor mixture is transferred to an aluminum oxide crucible and treated in a muffle furnace at 950°C for 15 hours to obtain a black powder layered oxide material Na 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zn 0.1 O2.

[0060] The high entropy layered oxide material prepared above is used as the positive electrode material of the battery. The specific steps are as follows: 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zn 0.1 O2 powder is mixed with acetylene black and polyvinylidene fluoride in a mass ratio of 95:2:3, and an appropriate amount of N-methylpyrrolidone solution is added to stir and form a slurry. The slurry is then evenly coated on aluminum foil and cut into electrodes after vacuum or blast drying. Dry at 80°C for 12 hours under vacuum conditions and then transfer to a glove box for use.

[0061] The battery was assembled in an argon atmosphere glove box, with a potassium metal sheet as the negative electrode and a NaPF6+5% KPF6 / diethyl carbonate solution as the electrolyte. The battery device was assembled. The charge and discharge cycle test was performed at a current density of 0.1 C for 10 cycles. The positive electrode was then removed, disassembled, crushed, cleaned, and finally dried to obtain Na 0. 9K 0.1 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zn 0.1 O2, the positive electrode is obtained and then the electrochemical performance is tested using metallic sodium as the negative electrode. Under the conditions of a discharge cut-off voltage of 1.5V and a charge cut-off voltage of 4.5V, the test results are shown in Table 1.

[0062] Example 4

[0063] In this embodiment, the layered oxide material is prepared by a spray drying method + an in-situ method, including:

[0064] The required sodium stoichiometric sodium carbonate (0.95 mol) and the required stoichiometric nickel acetate (0.35 mol), manganese acetate (0.3 mol), iron acetate (0.1 mol), copper acetate (0.05 mol), aluminum acetate (0.1 mol), and titanium nitrate (0.1 mol) are mixed into a precursor. The precursor is dissolved in water to obtain a transparent solution; the solution is placed in a spray dryer and spray-dried at 120°C; the sprayed precursor mixture is collected and transferred to an aluminum oxide crucible, and heat-treated at 950°C in an air atmosphere in a muffle furnace for 8 hours to obtain a gray-black powder layered oxide material, which is Na 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1Al 0. 1O2, and finally the high entropy Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Al 0.1 The O2 layered oxide material is used as the active material of the battery positive electrode material for the preparation of a sodium ion battery, and an electrochemical charge and discharge test is performed. The preparation process and test method are the same as those in Example 1. The test data are shown in Table 1.

[0065] Example 5

[0066] In this embodiment, the layered oxide material is prepared by a sol-gel method + an in-situ method, including:

[0067] The specific preparation steps of this embodiment are as follows: first, sodium acetate or sodium nitrate or sodium carbonate or sodium sulfate of 100wt% to 112wt% of the required sodium stoichiometry, and nitrates containing elements such as nickel, manganese, iron, copper, zinc, and titanium are dissolved in water in a stoichiometric ratio (nickel: manganese: iron: copper: zinc: titanium molar ratios are 0.35:0.3:0.1:0.05:0.1:0.1, respectively) to form a precursor solution, and then an appropriate amount of citric acid is added as a chelating agent, and the mixture is placed in an oil bath at 90°C and stirred; the dried gel obtained by evaporation is transferred to an aluminum oxide crucible and pre-fired at 180°C for 3 hours; and then heat-treated at 950°C in an air atmosphere in a muffle furnace for 12 hours to obtain a brown-black powder layered oxide material Na 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zn 0.1 O2, and finally the high entropy Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zn 0.1 The O2 layered oxide material is used as the active material of the battery positive electrode material for the preparation of a sodium ion battery, and an electrochemical charge and discharge test is performed. The preparation process and test method are the same as those in Example 1. The test data are shown in Table 1.

[0068] Example 6

[0069] In this embodiment, the layered oxide material is prepared by a co-precipitation method + an in-situ method, including:

[0070] According to the stoichiometric ratio (the molar ratios of nickel: manganese: iron: copper: zinc: titanium are 0.35:0.3:0.1:0.05:0.1:0.1 respectively), the required nickel, manganese, iron, copper, aluminum, and titanium nitrates are dissolved in a certain volume of deionized water to form solutions. The solutions are mixed together, and ammonia water is slowly added to the solution until the pH of the solution is 10; after the reaction is completed, the generated precipitate is taken out and filtered and washed with deionized water, and then placed in a vacuum oven at 80°C for drying; the dried powder is evenly mixed with sodium carbonate (5% excess) according to the stoichiometric ratio to obtain a precursor; the precursor mixture is then transferred to a muffle furnace for heat treatment at 950°C for 20 hours. The powder after heat treatment is ground to obtain a brown-black layered oxide material, which is Na 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Al 0.1 O2, and finally the high entropy Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Al 0.1 The O2 layered oxide material is used as the active material of the battery positive electrode material for the preparation of a sodium ion battery, and an electrochemical charge and discharge test is performed. The preparation process and test method are the same as those in Example 1. The test data are shown in Table 1.

[0071] Example 7

[0072] In this embodiment, a high temperature solid phase method + in-situ method is used to prepare the layered oxide material.

[0073] The specific preparation steps of the embodiment are the same as those of embodiment 1, but the oxide of M is selected from magnesium oxide, the raw material is analytically pure, and the stoichiometric amount of magnesium oxide is 0.1 mol, to obtain a black powder layered oxide material Na 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Mg 0. 1O2.

[0074] The layered oxide material prepared above was used as the positive electrode material of the battery and a high entropy Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Mg0.1 O2 material. Its preparation process and test method are the same as those in Example 1, and the test results are shown in Table 1.

[0075] Example 8

[0076] In this embodiment, a high temperature solid phase method + in-situ method is used to prepare the layered oxide material.

[0077] The specific preparation steps of the embodiment are the same as those of embodiment 1, but the oxide of M is selected from vanadium dioxide, the raw material is analytically pure, and the stoichiometric amount of vanadium dioxide is 0.1 mol, to obtain a black powder layered oxide material Na 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0. 1V 0.1 O2.

[0078] The layered oxide material prepared above was used as the positive electrode material of the battery and a high entropy Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 V 0.1 O2 material. Its preparation process and test method are the same as those in Example 1, and the test results are shown in Table 1.

[0079] Example 9

[0080] In this embodiment, a high temperature solid phase method + in-situ method is used to prepare the layered oxide material.

[0081] The specific preparation steps of the embodiment are the same as those of embodiment 1, but the oxide of M is zirconium dioxide, the raw material is analytically pure, and the stoichiometric amount of zirconium dioxide is 0.1 mol, and a black powder layered oxide material Na 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zr 0.1 O2.

[0082] The layered oxide material prepared above was used as the positive electrode material of the battery and a high entropy Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zr 0.1O2 material. Its preparation process and test method are the same as those in Example 1, and the test results are shown in Table 1.

[0083] Example 10

[0084] In this embodiment, a high temperature solid phase method + in-situ method is used to prepare the layered oxide material.

[0085] The specific preparation steps of the embodiment are the same as those of embodiment 1, but the oxide of M is selected from chromium trioxide, the raw material is analytically pure, and the stoichiometric amount of chromium trioxide is 0.1 mol, to obtain a black powder layered oxide material Na 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Cr 0.1 O2.

[0086] The layered oxide material prepared above was used as the positive electrode material of the battery and a high entropy Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Cr 0.1 O2 material. Its preparation process and test method are the same as those in Example 1, and the test results are shown in Table 1.

[0087] Embodiment 11

[0088] In this embodiment, a high temperature solid phase method + in-situ method is used to prepare the layered oxide material.

[0089] The specific preparation steps of the embodiment are the same as those of embodiment 1, but the oxide of M is selected from niobium pentoxide, the raw material is analytically pure, and the stoichiometric amount of niobium pentoxide is 0.1 mol, and a black powder layered oxide material Na 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Nb 0.1 O2.

[0090] The layered oxide material prepared above was used as the positive electrode material of the battery and a high entropy Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Nb 0.1O2 material. Its preparation process and test method are the same as those in Example 1, and the test results are shown in Table 1.

[0091] Example 12

[0092] In this embodiment, a high temperature solid phase method + in-situ method is used to prepare the layered oxide material.

[0093] The specific preparation steps of the embodiment are the same as those of embodiment 1, but the oxide of M is selected from molybdenum dioxide, the raw material is analytically pure, and the stoichiometric amount of molybdenum dioxide is 0.1 mol, to obtain a black powder layered oxide material Na 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Mo 0.1 O2.

[0094] The layered oxide material prepared above was used as the positive electrode material of the battery and a high entropy Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Mo 0.1 O2 material. Its preparation process and test method are the same as those in Example 1, and the test results are shown in Table 1.

[0095] Example 13

[0096] In this embodiment, a high temperature solid phase method + in-situ method is used to prepare the layered oxide material.

[0097] The specific preparation steps of the embodiment are the same as those of embodiment 1, but the oxide of M is selected from ruthenium dioxide, the raw material is analytically pure, and the stoichiometric amount of ruthenium dioxide is 0.1 mol, and a black powder layered oxide material Na 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Ru 0.1 O2.

[0098] The layered oxide material prepared above was used as the positive electrode material of the battery and a high entropy Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Ru 0.1O2 material. Its preparation process and test method are the same as those in Example 1, and the test results are shown in Table 1.

[0099] Embodiment 14

[0100] In this embodiment, a high temperature solid phase method + in-situ method is used to prepare the layered oxide material.

[0101] The specific preparation steps of the embodiment are the same as those of embodiment 1, but the oxide of M is selected as tin dioxide, the raw material is analytically pure, and the stoichiometric amount of tin dioxide is 0.1 mol, and a black powder layered oxide material Na 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Sn 0.1 O2.

[0102] The layered oxide material prepared above was used as the positive electrode material of the battery and a high entropy Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Sn 0.1 O2 material. Its preparation process and test method are the same as those in Example 1, and the test results are shown in Table 1.

[0103] Embodiment 15

[0104] In this embodiment, a high temperature solid phase method + in-situ method is used to prepare the layered oxide material.

[0105] The specific preparation steps of the embodiment are the same as those of embodiment 1, but the oxide of M is selected from antimony pentoxide, the raw material is analytically pure, and the stoichiometric amount of antimony pentoxide is 0.1 mol, to obtain a black powder layered oxide material Na 0.9 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Sb 0.1 O2.

[0106] The layered oxide material prepared above was used as the positive electrode material of the battery and a high entropy Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Sb 0.1O2 material. Its preparation process and test method are the same as those in Example 1, and the test results are shown in Table 1.

[0107] Comparative Example 1

[0108] In this comparative example, a high temperature solid phase method is used to prepare a layered oxide material, including:

[0109] Sodium carbonate, potassium carbonate, nickel oxide, manganese oxide, iron oxide, titanium oxide, copper oxide, and magnesium oxide are mixed in the required stoichiometric ratio (sodium carbonate 0.95 mol, potassium carbonate 0.07 mol, nickel oxide 0.35 mol, manganese oxide 0.3 mol, iron oxide 0.1 mol, titanium oxide 0.1 mol, copper oxide 0.05 mol, and magnesium oxide 0.1 mol); ball milling is performed on a ball mill at 400 rpm for 10 hours to obtain a precursor; the precursor mixture is transferred to an aluminum oxide crucible and treated in a muffle furnace at 950°C for 15 hours to obtain a black powder layered oxide material Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Mg 0.1 O2. Finally, the layered oxide material prepared as above was used as the active material of the battery positive electrode material for the preparation of sodium ion battery, and electrochemical charge and discharge tests were carried out. The test data are shown in Table 1.

[0110] Comparative Example 2

[0111] In this comparative example, a high temperature solid phase method is used to prepare a layered oxide material, including:

[0112] Sodium carbonate, potassium carbonate, nickel oxide, manganese oxide, iron oxide, titanium oxide, copper oxide, and zinc oxide are mixed in the required stoichiometric ratio (sodium carbonate 0.95 mol, potassium carbonate 0.02 mol, nickel oxide 0.35 mol, manganese oxide 0.3 mol, iron oxide 0.1 mol, titanium oxide 0.1 mol, copper oxide 0.05 mol, and zinc oxide 0.1 mol); ball milling is performed on a ball mill at 400 rpm for 10 hours to obtain a precursor; the precursor mixture is transferred to an aluminum oxide crucible and treated in a muffle furnace at 950°C for 15 hours to obtain a black powder layered oxide material Na 0.9 K 0.02 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zn 0.1O2. Finally, the layered oxide material prepared as above was used as the active material of the battery positive electrode material for the preparation of sodium ion battery, and electrochemical charge and discharge tests were carried out. The test data are shown in Table 1.

[0113] Comparative Example 3

[0114] In this comparative example, a high temperature solid phase method is used to prepare a layered oxide material, including:

[0115] Sodium carbonate, potassium carbonate, nickel oxide, manganese oxide, iron oxide, titanium oxide, copper oxide, and zinc oxide are mixed in the required stoichiometric ratio (sodium carbonate 0.95 mol, potassium carbonate 0.1 mol, nickel oxide 0.35 mol, manganese oxide 0.3 mol, iron oxide 0.1 mol, titanium oxide 0.1 mol, copper oxide 0.05 mol, zirconium oxide 0.1 mol); ball milling is performed on a ball mill at 400 rpm for 10 hours to obtain a precursor; the precursor mixture is transferred to an aluminum oxide crucible and treated in a muffle furnace at 950°C for 15 hours to obtain a black powder layered oxide material Na 0.9 K 0.1 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zn 0.1 O2. Finally, the layered oxide material prepared as above was used as the active material of the battery positive electrode material for the preparation of sodium ion battery, and electrochemical charge and discharge tests were carried out. The test data are shown in Table 1.

[0116] Comparative Example 4

[0117] In this comparative example, a spray drying method is used to prepare a layered oxide material, comprising:

[0118] The precursor is prepared by mixing sodium carbonate, potassium carbonate and nickel acetate, manganese acetate, iron acetate, copper acetate, aluminum acetate, titanium nitrate, etc. in the required stoichiometric ratio of sodium (nickel: manganese: iron: copper: aluminum: titanium molar ratio of 0.35:0.3:0.1:0.05:0.1:0.1, respectively). The precursor is dissolved in water to obtain a transparent solution; the solution is placed in a spray dryer and spray-dried at 120°C; the sprayed precursor is collected and transferred to an aluminum oxide crucible, and heat-treated at 950°C in an air atmosphere in a muffle furnace for 8 hours to obtain a high entropy Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Al 0.1O2 layered oxide materials were used as active materials for the positive electrode materials of batteries in the preparation of sodium ion batteries, and electrochemical charge and discharge tests were performed. The data are shown in Table 1.

[0119] Comparative Example 5

[0120] In this comparative example, a coprecipitation method is used to prepare a layered oxide material, comprising:

[0121] According to the stoichiometric ratio (the molar ratios of nickel: manganese: iron: copper: aluminum: titanium are 0.35:0.3:0.1:0.05:0.1:0.1 respectively), the required nickel, manganese, iron, copper, aluminum, and titanium nitrates are dissolved in a certain volume of deionized water to form solutions. The solutions are mixed together, and ammonia water is slowly added to the solution until the pH of the solution is 10; after the reaction is completed, the generated precipitate is taken out and filtered and washed with deionized water, and then placed in a vacuum oven at 80°C for drying; the dried powder is evenly mixed with sodium carbonate and potassium carbonate (both in excess of 5%) according to the stoichiometric ratio to obtain a precursor; the precursor mixture is then transferred to a muffle furnace for heat treatment at 950°C for 20 hours. The heat-treated powder is ground to obtain a high-entropy Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.0 5Ti 0.1 Al 0.1 O2 layered oxide materials were used as active materials for the positive electrode materials of batteries in the preparation of sodium ion batteries, and electrochemical charge and discharge tests were performed. The data are shown in Table 1.

[0122] Comparative Example 6

[0123] In this comparative example, a high temperature solid phase method was used to prepare the layered oxide material.

[0124] The specific preparation steps of the comparative example are the same as those of comparative example 1, but the oxide of M is selected from vanadium oxide, the raw material is analytically pure, and the stoichiometric amount of vanadium oxide is 0.1 mol, to obtain a black powder layered oxide material Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0. 1V 0.1 The test method is the same as that of Comparative Example 1, and the test results are shown in Table 1.

[0125] Comparative Example 7

[0126] In this comparative example, a high temperature solid phase method was used to prepare the layered oxide material.

[0127] The specific preparation steps of the comparative example are the same as those of comparative example 1, but the oxide of M is zirconium oxide, the raw material is analytically pure, and the stoichiometric amount of zirconium oxide is 0.1 mol, and a black powder layered oxide material Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Zr 0.1 The test method is the same as that of Comparative Example 1, and the test data are shown in Table 1.

[0128] Comparative Example 8

[0129] In this comparative example, a high temperature solid phase method was used to prepare the layered oxide material.

[0130] The specific preparation steps of the comparative example are the same as those of comparative example 1, but the oxide of M is selected from chromium trioxide, the raw material is analytically pure, and the stoichiometric amount of chromium trioxide is 0.1 mol, and a black powder layered oxide material Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Cr 0.1 The test method is the same as that of Comparative Example 1, and the test data are shown in Table 1.

[0131] Comparative Example 9

[0132] In this comparative example, a high temperature solid phase method was used to prepare the layered oxide material.

[0133] The specific preparation steps of the comparative example are the same as those of comparative example 1, but the oxide of M is selected as niobium pentoxide, the raw material is analytically pure, and the stoichiometric amount of niobium pentoxide is 0.1 mol, and a black powder layered oxide material Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Nb 0.1 The test method is the same as that of Comparative Example 1, and the test data are shown in Table 1.

[0134] Comparative Example 10

[0135] In this comparative example, a high temperature solid phase method was used to prepare the layered oxide material.

[0136] The specific preparation steps of the comparative example are the same as those of comparative example 1, but the oxide of M is selected as molybdenum dioxide, the raw material is analytically pure, and the stoichiometric amount of molybdenum dioxide is 0.1 mol, and a black powder layered oxide material Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Mo 0.1 The test method is shown in Comparative Example 1, and the test data is shown in Table 1.

[0137] Comparative Example 11

[0138] In this comparative example, a high temperature solid phase method was used to prepare the layered oxide material.

[0139] The specific preparation steps of the comparative example are the same as those of comparative example 1, but the oxide of M is selected from ruthenium dioxide, the raw material is analytically pure, and the stoichiometric amount of ruthenium dioxide is 0.1 mol, and a black powder layered oxide material Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Ru 0.1 The test method is shown in Comparative Example 1, and the test data is shown in Table 1.

[0140] Comparative Example 12

[0141] In this comparative example, a high temperature solid phase method was used to prepare the layered oxide material.

[0142] The specific preparation steps of the comparative example are the same as those of comparative example 1, but the oxide of M is tin dioxide, the raw material is analytically pure, and the stoichiometric amount of tin dioxide is 0.1 mol, to obtain a black powder layered oxide material Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Sn 0.1 The test method is the same as that of Comparative Example 1, and the test data are shown in Table 1.

[0143] Comparative Example 13

[0144] In this comparative example, a high temperature solid phase method was used to prepare the layered oxide material.

[0145] The specific preparation steps of the comparative example are the same as those of comparative example 1, but the oxide of M is selected from antimony pentoxide, the raw material is analytically pure, and the stoichiometric amount of antimony pentoxide is 0.1 mol, to obtain a black powder layered oxide material Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.3 Cu 0.05 Ti 0.1 Sb 0.1 The test method is shown in Comparative Example 1, and the test data is shown in Table 1.

[0146] Comparative Example 14

[0147] This comparative example adopts a high temperature solid phase method + in-situ method to prepare the layered oxide material.

[0148] The specific preparation steps of this comparative example are the same as those of Example 1, except that the raw materials and the stoichiometric ratios are 0.95 mol of sodium carbonate, 0.35 mol of nickel oxide, 0.55 mol of manganese oxide, and 0.1 mol of iron oxide, and the raw materials are all analytically pure, to obtain a black powder layered oxide material Na 0.9 Ni 0.35 Fe 0.1 Mn 0.55 O2.

[0149] The layered oxide material prepared above was used as the positive electrode material of the battery and the highest entropy Na 0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.55 O2 material. Its preparation process and test method are the same as those in Example 1, and the test results are shown in Table 1.

[0150] Comparative Example 15

[0151] This comparative example adopts a high temperature solid phase method + in-situ method to prepare the layered oxide material.

[0152] The specific preparation steps of this comparative example are the same as those of Example 1, but the raw materials and the stoichiometric ratios are 0.95 mol of sodium carbonate, 0.35 mol of nickel oxide, 0.45 mol of manganese oxide, 0.1 mol of iron oxide, and 0.1 mol of titanium oxide, and the raw materials are all analytically pure, and a black powder layered oxide material Na 0.9 Ni 0.35 Fe 0.1 Mn 0.45 Ti 0.1 O2.

[0153] The layered oxide material prepared above was used as the positive electrode material of the battery and a high entropy Na0.9 K 0.07 Ni 0.35 Fe 0.1 Mn 0.45 Ti 0.1 O2 material. Its preparation process and test method are the same as those in Example 1, and the test results are shown in Table 1.

[0154] The following table shows the discharge test results of various embodiments and comparative examples.

[0155] Table 1 Charge and discharge test results of various embodiments and comparative examples

[0156]

[0157] The present invention dopes a potassium metal element with a large ion radius into the sodium layer in the form of charge and discharge to enhance the layered structure. The sodium ion secondary battery using the high entropy layered oxide material of the present invention has good cycle performance, good safety performance, high average discharge voltage, and great practical potential, providing new ideas and references for subsequent different doping methods.

[0158] The specific implementation methods described above further illustrate the objectives, technical solutions and beneficial effects of the present invention in detail. It should be understood that the above description is only a specific implementation method of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the scope of protection of the present invention.

Claims

1. A high entropy layered oxide material, characterized in that: The general chemical formula of the high entropy layered oxide material is: Na a K x Ni b Fe c Mn d Cu e Ti f M g O 2+β , by doping the sodium layer with a large ion radius of potassium metal to stabilize the layered structure, the charging and discharging method is as follows: the undoped K element layered oxide material Na a Ni b Fe c Mn d Cu e Ti f M g O 2+β The positive electrode and potassium sheet are electrochemically assembled, the electrolyte is NaPF6+5% KPF6, the solvent is ethylene carbonate and diethyl carbonate, and 0.1C charging and discharging is performed in the voltage range of 1.5-4.5V. After 2-10 cycles, the material is disassembled, crushed, cleaned and thoroughly dried to obtain the high entropy layered oxide material. Among them, K is located in the sodium layer, Ni 、 Fe 、 Mn 、 Cu 、 Ti 、 M is located in the transition metal layer, and M is a substitution element, specifically one or more elements selected from magnesium, zinc, vanadium, chromium, zirconium, niobium, molybdenum, ruthenium, tin, antimony, and aluminum; a, b, c, d, e, f, g, x, and β are the molar percentages of the corresponding elements respectively, and the relationship between the molar percentages satisfies b + c + d + e + f + g = 1, and a + x + 2b + 3c + 4d + 2e + 4f + mg = 2(2 + β); where 0.7 < a ≤ 1; 0 < x ≤ 0.1; 0.05 < b ≤ 0.35; 0.05 < c ≤ 0.2; 0.05 < d ≤ 0.35; 0 < e ≤ 0.1; 0.05 < f ≤ 0.2; 0 < g ≤ 0.1; -0.02 ≤ β ≤ 0.02; m is the valence state of the M element; The crystal structure of the high-entropy layered oxide material is the O3 phase, and the space group is R3m.

2. The high entropy layered oxide material according to claim 1, characterized in that: The high-entropy layered oxide material is used as the positive electrode active material for a sodium-ion secondary battery.

3. A method for preparing a high entropy layered oxide material as claimed in claim 1, characterized in that: The method is a solid-phase method + in-situ method, including: Mix 90 wt% - 112 wt% of sodium carbonate of the stoichiometric amount of sodium required and the stoichiometric amounts of nickel oxide, manganese dioxide, iron(III) oxide, titanium dioxide, copper oxide, and the oxide of M in proportion to form a precursor; M is specifically one or more of magnesium, zinc, vanadium, chromium, zirconium, niobium, molybdenum, ruthenium, tin, antimony, and aluminum elements; Use ball milling to uniformly mix the precursor to obtain a precursor powder; Place the precursor powder in a muffle furnace and heat-treat it in an air atmosphere at 600°C - 1000°C for 5 - 25 hours; grind and sieve the heat-treated precursor powder to obtain Material A; Fabricate the Material A into a positive electrode, use a potassium sheet as the negative electrode for electrochemical assembly, the electrolyte used is a solution of 1.0 mol / L NaPF6 + 5% KPF6 dissolved in ethylene carbonate and diethyl carbonate, and perform 0.1C charge and discharge in the voltage range of 1.5 - 4.5V. After 2 - 10 cycles, disassemble, crush, remove impurities and clean, and obtain the high-entropy layered oxide material after sufficient drying.

4. A method for preparing a high entropy layered oxide material as claimed in claim 1, characterized in that: The method is a spray-drying method + in-situ method, including: Mix sodium nitrate, nickel acetate, manganese acetate, iron acetate, copper acetate, titanium nitrate, and the nitrate or acetate of M in stoichiometric ratio as the precursor; M is specifically one or more of magnesium, zinc, vanadium, chromium, zirconium, niobium, molybdenum, ruthenium, tin, antimony, and aluminum elements; Add ethanol or water to the precursor mixture and stir evenly to form a slurry; Perform spray drying on the slurry to obtain a precursor powder; Place the precursor powder in a muffle furnace and heat-treat it in an air atmosphere at 600°C - 1000°C for 5 - 25 hours; Grind and sieve the heat-treated precursor powder to obtain Material B; Fabricate the Material B into a positive electrode, use a potassium sheet as the negative electrode for electrochemical assembly, the electrolyte used is a solution of 1.0 mol / L NaPF6 + 5% KPF6 dissolved in ethylene carbonate and diethyl carbonate, and perform 0.1C charge and discharge in the voltage range of 1.5 - 4.5V. After 2 - 10 cycles, disassemble, crush, remove impurities and clean, and obtain the high-entropy layered oxide material after sufficient drying.

5. A method for preparing a high entropy layered oxide material as claimed in claim 1, characterized in that: The method is a sol-gel method + in-situ method, including: Sodium acetate or sodium nitrate or sodium carbonate or sodium sulfate with a stoichiometric amount of 90 wt% to 112 wt% of the required sodium, and nitrates or sulfates containing nickel, manganese, iron, copper, titanium and M elements are dissolved in water or ethanol according to a stoichiometric ratio to form a precursor solution; the M is specifically one or more of magnesium, zinc, vanadium, chromium, zirconium, niobium, molybdenum, ruthenium, tin, antimony, and aluminum elements; The precursor solution is stirred at 50° C. to 100° C., a chelating agent is added, and evaporated to form a precursor gel; The precursor gel is placed in a crucible, pre-calcined for 1-3 hours in an air atmosphere at 100-600° C., and then heat-treated at 600-1000° C. for 5-25 hours to obtain a precursor powder; Grinding and sieving the precursor powder to obtain C material; The C material is made into a positive electrode, and a potassium sheet is used as a negative electrode for electrochemical assembly. The electrolyte used is a solution of 1.0 mol / L NaPF6+5% KPF6 dissolved in ethylene carbonate and diethyl carbonate. The battery is charged and discharged at 0.1C in the voltage range of 1.5-4.5V. After 2-10 cycles, the battery is disassembled, crushed, cleaned, and fully dried to obtain the high-entropy layered oxide material.

6. A method for preparing a high entropy layered oxide material as claimed in claim 1, characterized in that: The method is a co-precipitation method + in-situ method, comprising: Dissolve nitrates or sulfates or carbonates or hydroxides containing nickel, manganese, iron, copper, titanium and elements in the required stoichiometric ratio in water to form solutions; wherein M is specifically one or more of magnesium, zinc, vanadium, chromium, zirconium, niobium, molybdenum, ruthenium, tin, antimony and aluminum; The solution was slowly added dropwise to an ammonia solution with a pH value of 6-10 to generate a precipitate; The obtained precipitate is cleaned with water, dried, and then uniformly mixed with sodium carbonate in a stoichiometric ratio to obtain a precursor; The precursor is placed in a crucible and heat treated for 5 to 25 hours in an air atmosphere at 600° C. to 1000° C. to obtain a precursor powder; Grinding and sieving the precursor powder to obtain material D; The D material is made into a positive electrode, and a potassium sheet is used as a negative electrode for electrochemical assembly. The electrolyte used is a solution of 1.0 mol / L NaPF6+5% KPF6 dissolved in ethylene carbonate and diethyl carbonate. The material is charged and discharged at 0.1C in the voltage range of 1.5-4.5V. After 2-10 cycles, it is disassembled, crushed, cleaned and thoroughly dried to obtain the high-entropy layered oxide material.

7. The present invention provides a positive electrode sheet for a sodium ion secondary battery, the positive electrode sheet comprising: A current collector, a conductive additive coated on the current collector, a binder and the high entropy layered oxide material according to claim 1.

8. A sodium ion secondary battery comprising the positive electrode sheet according to claim 7.

Citation Information

Patent Citations

  • Difunctional high-entropy nano-alloy electrocatalyst and preparation method thereof

    CN116288477A

  • Sb and Ti co-doped high-entropy layered oxide sodium ion battery positive electrode material and preparation method thereof

    CN116845202A